Research and development in science education: East asian perspectives - Khine, Myint Swe (2015)
The results from the international benchmarking tests on mathematics and science achievements such as the Trends in International Mathematics and Science Study (TIMSS) and Programme for International Student Assessment (PISA) revealed that students from East Asian countries consistently outperformed their counterparts in each and every cycle of the study. Among the high-achieving countries, the performances of the students in Singapore, Taiwan, Korea, Japan, and Hong Kong are recognized by the international education community. Some educators believe that the success of these countries is deeply rooted in eastern philosophy and cultural notion of education and influence of parental encouragements. Some think that the reasons are multifaceted including instructional practices, classroom climates, and the curriculum. Scientific explanations will provide insights into how these educational systems are functioning in improving the standard and achievement in science subjects in schools. This book attempts to bring together prominent science educators and researchers from the East Asia to share their experience and findings, reflection and vision on emerging trends, research-informed pedagogical innovations, and best practices in science education in the region.